Statistical Inference on the Shape Parameter of Inverse Generalized Weibull Distribution - Yan Zhuang; Sudeep R. Bapat; Wenjie Wang (Mathematics, 2024)
In this paper, we propose statistical inference methodologies for estimating the shape parameter <semantics>α</semantics> of inverse generalized Weibull (IGW) distribution. Specifically, we develop two approaches: (1) a bounded-risk point estimation strategy for <semantics>α</semantics> and (2) a fixed-accuracy confidence interval estimation method for <semantics>α</semantics>. For (1), we introduce a purely sequential estimation strategy, which is theoretically shown to possess desirable first-order efficiency properties. For (2), we present a method that allows for the precise determination of sample size without requiring prior knowledge of the other two parameters of the IGW distribution. To validate the proposed methods, we conduct extensive simulation studies that demonstrate their effectiveness and consistency with the theoretical results. Additionally, real-world data applications are provided to further illustrate the practical applicability of the proposed procedures.